Secrets of ProShow experts [ the official guide to creating your best slide shows with ProShow 5 - Schmidt, Paul (Course Technology/Cengage Learning, 2013)
Shows you how to harness the full power of ProShow. This title offers tips for creating slide shows, with examples and expert advice on topics like understanding your audience, using motion to convey emotion, controlling the feel of a slide show with audio, and more.